Characterization of shear strength between induction coils and asphalt layers in electric roads for charging electric vehicles in motion (2025)
ABSTRACT : Electric Road Systems (ERS) are an innovative technology designed to enable in-motion charging of electric vehicles through induction coils embedded in road pavements. This study focuses on characterizing the shear strength of interlayers between asphalt and the rubber casing of these coils, evaluating different bonding agents and techniques to assess their impact on durability and performance. The inclusion of rubber coils as interlayers in asphalt significantly reduces shear strength, with observed reductions of up to 88% compared to traditional asphalt-asphalt interfaces using emulsion as a bonding agent. The use of bituminous membranes demonstrated improved performance over emulsion bonding (when comparing identical interlayer materials) and exhibited a recovery factor, allowing the membrane to regain its original position after deformation. This indicates potential benefits in durability and adaptability under certain conditions, though further testing is needed to confirm these findings. The reduced shear strength associated with rubber coils raises concerns about the potential shortening of the service life of roads incorporating this technology. Improved bonding agents could mitigate these issues by enhancing adhesion and interlayer stress resistance. Advancing bonding materials represents a key opportunity for the industry to address these challenges, ensuring better durability and structural integrity for electric roads. This research highlights both the opportunities and challenges associated with integrating induction coil systems into pavement layers, providing valuable insights for the advancement of sustainable transportation infrastructure.